Гак для натягування арбалета з малого городища у Буську - Калініченко, Віталій; Стеблій, Наталія; Довгань, Петро (Київ, Інститут історії України НАН України, 2020)
Since 2015, the Busk archaeological expedition of the Institute of Archaeology of the Ivan Franko National University in Lviv has explored the Small Hillfort – one of the components of the Busk archaeological complex. During the excavations it was found out that the upper cultural and chronological horizons of the monument are the so-called «Conical Hillfort» of the 14th century. From the cultural layer of this hillfort comes a rare crossbow tensioning hook, found on the crest of the shaft. Its typology and interpretation are given. As a result, it was found that the hook belongs to the period of 14-15th centuries and was used for a light (original) crossbow. The chronology of the use of the crossbow hook in the Small Hillfort is specified by a spur with an asterisk, which according to the existing classification schemes dates back to the second half of the 14-50th years of the 15th century. The stratigraphy and planigraphy of the discovery of the hook, as well as the crossbow bolts in the Small Hillfort, may indicate that they appeared here as a result of its assault, during which the gate and the adjacent territory were the main strategic stronghold.
The сrossbow hook from a Small hillfort of Busk
Keywords: археологічні дослідження; озброєння; Буський археологічний комплекс; арбалетне озброєння; гак для натягування арбалета